Suggestive association between OPRM1 and impulse control disorders in Parkinson's disease. Issue 12 (16th November 2018) - Cormier‐Dequaire, Florence; Bekadar, Samir; Anheim, Mathieu; Lebbah, Said; Pelissolo, Antoine; Krack, Paul; Lacomblez, Lucette; Lhommée, Eugénie; Castrioto, Anna; Azulay, Jean‐Philippe; Defebvre, Luc; Kreisler, Alexandre; et al.
ABSTRACT: Background: Impulse control disorders are frequently associated with dopaminergic therapy in Parkinson's disease. Genetic studies have suggested a high heritability of impulse control disorders in the general population and in PD. The aim of this study was to identify candidate gene variants associated with impulse control disorders and related behaviors in PD. Methods: We performed a multicenter case‐control study in PD patients with (cases) or without impulse control disorders and related behaviors despite significant dopamine agonist exposure of >300 mg levodopa‐equivalent daily dose during 12 months (controls). Behavioral disorders were assessed using the Ardouin scale. We investigated 50 variants in 24 candidate genes by a multivariate logistic regression analysis adjusted for sex and age at PD onset. Results: The analysis was performed on 172 cases and 132 controls. Cases were younger (60 ± 8 vs 63 ± 8 years; P < 0.001) and had a higher family history of pathological gambling (12% vs 5%, P = 0.03). No variant was significantly associated with impulse control disorders or related behaviors after correction for multiple testing, although the 2 top variants were close to significant ( OPRM1 rs179991, OR, 0.49; 95%CI, 0.32‐0.76; P = 0.0013; Bonferroni adjusted P = 0.065; DAT1 40‐base pair variable number tandem repeat, OR, 1.82; 95%CI, 1.24‐2.68; P = 0.0021; Bonferroni adjusted P = 0.105). Conclusions: Our results are suggestive of a novel association of the opioid receptor gene OPRM1 with impulse control disorders and related behaviors in PD and confirm a previous association with DAT1 . Although replication in independent studies is needed, our results bring potential new insights to the understanding of molecular mechanisms of impulse control disorders. © 2018 International Parkinson and Movement Disorder Society